A sustainable alternative for cooling the machining processes using a refrigerant fluid in recirculation inside the toolholder - Vicentin, G. C. [UNESP]; Sanchez, L. E. A. [UNESP]; Scalon, V. L. [UNESP]; Abreu, G. G. C. [UNESP] (Springer, 2011)
This article presents a cooling system for cutting tool in turning based in a toolholder with cooling fluid flowing inside its body being that this fluid must necessarily be able to phase change due to heat generated from machining processes. In this way, the fluid evaporates just under the cutting tool allowing a heat transfer more efficient than if were used a fluid without phase change once the latent heat of evaporation is beneficial for removal heat. Following, the cooling fluid evaporated passes through a condenser located out of the toolholder where it is condensated and returns to the toolholder again and a new cycle is started. In this study, the R-123, a hydrochlorofluorocarbon (HCFC) fluid, was selected for the turning of a Cr-Ni-Nb-Mn-N austenitic steel of hard machinability. The machining tests were carried out under three different machining conditions: dry machining, external cutting fluid (conventional method), and with the toolholder proposed. As result, the developed system allows a surface roughness up to 10% better than dry machining and a tool life close to the conventional method, but 32% superior to dry machining; moreover, there are environmental and economics advantages once the cooling fluid is maintained in a loop circuit.
Keywords: Turning; Internal cooling; Dry machining; Tool life; Coolant fluid